E-shop – E Commerce and Management System - Athapaththu A.H.M.C.P.; Jayashantha D.A.C.N.; Herath H.P.N.U.; Dunusinghe A.V.; De Silva D.I.; Samarasekara H.M.P.P.K.H. (International Journal of Engineering and Management Research, 2022)
The main focus of the paper, “E-shop is an e-commerce web application designed for an online electronic store based on a client's requirement. E-commerce, a fast-growing business trend over the last decade, and many companies switching to this since it is a supporting tool in marketing and business strategy to grow their businesses by transforming traditional business transactions into online transactions and making a good reputation on their brand as well. This application is a combination of a website where customers can place their orders and an administration management system where the admin can manage; he/she tasks related to the store. The system is developed to make it easier for administrators as well to keep track of everyday activities including orders, deliveries, existing and new users, customer care services, products in the store, payments and reports, etc. This essay discusses the steps involved in user management and registrations, placing orders, arranging deliveries of the placed orders, and payments related to orders. After considering the stocks available, administrators are able to accept or reject the order that the customer placed, and the status of the order, delivery, and payment will be updated to users by sending notifications and emails.